TRIPLE MARGINALISASI PEREMPUAN PENYANDANG DISABILITAS: ANALISIS IMPLEMENTASI KEBIJAKAN KETENAGAKERJAAN DI KOTA PALANGKA RAYA - Bagas Rizky Ardiansyah; Setianingsih Setianingsih; Suprayitno Suprayitno; Subhan Ilham Thareq (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2026)
Inclusive employment policy in Palangka Raya City has not yet been able to provide equal employment access for persons with disabilities, particularly women. Various structural and substantive barriers continue to limit their participation in the formal labor sector. This study aims to analyze the implementation of inclusive employment policy and to examine the forms of marginalization experienced by women with disabilities. The study employed a qualitative approach using a case study design. Data were collected through in-depth interviews, observation, and document analysis involving nine informants directly related to policy implementation. The analysis was conducted using George C. Edwards III’s policy implementation model, which includes communication, resources, disposition, and bureaucratic structure, and was strengthened by Kimberlé Crenshaw’s intersectionality perspective. The findings reveal that policy implementation has not been carried out optimally due to ineffective policy communication, limited resources, weak institutional support, and the absence of local technical regulations. Under these conditions, women with disabilities experience multiple forms of marginalization resulting from the intersection of gender, disability, and weaknesses in policy implementation. This study highlights the importance of strengthening institutional capacity and developing policies that are more responsive to gender and disability vulnerabilities. Keywords: Inclusive Employment Policy; Triple Marginalization; Women With Disabilities.